A review of chemical absorption of carbon dioxide for biogas upgrading - Abdeen, Fouad R. H.; Mel, Maizirwan; Jami, Mohammed Saedi; Ihsan, Sany Izan; Ismail, Ahmad Faris (Chemical Industry Press, 2016)
Significant attention has been given to biogas production, purification and upgrading as a renewable and clean fuel supplement. Biogas is a product of an anaerobic digestion process comprising methane, carbon dioxide, and trace amounts of other gases. Biogas purification removes trace gases in biogas for safe utilisation. Biogas upgrading produces methane-rich biogas by removing bulk carbon dioxide from the gas mixture. Several carbon dioxide removal techniques can be applied for biogas upgrading. However, chemical absorption of carbon dioxide for biogas upgrading is of special significance due to its operation at ambient or near ambient temperature and pressure, thus reducing energy consumption. This paper reviews the chemical absorption of carbon dioxide using amine scrubbing, caustic solvents scrubbing, and amino acid salts solutions scrubbing. Each of these techniques for biogas upgrading are discussed. The paper concludes that an optimised implementation of the chemical absorption techniques for biogas upgrading requires further research.